2012
DOI: 10.1073/pnas.1121471109
|View full text |Cite
|
Sign up to set email alerts
|

Biotinylation of lysine method identifies acetylated histone H3 lysine 79 in Saccharomyces cerevisiae as a substrate for Sir2

Abstract: Although the biological roles of many members of the sirtuin family of lysine deacetylases have been well characterized, a broader understanding of their role in biology is limited by the challenges in identifying new substrates. We present here an in vitro method that combines biotinylation and mass spectrometry (MS) to identify substrates deacetylated by sirtuins. The method permits labeling of deacetylated residues with amine-reactive biotin on the ϵ-nitrogen of lysine. The biotin can be utilized to purify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 65 publications
1
12
0
Order By: Relevance
“…Acetylation of K23 and K79 on H3 and K31 on H4 are novel histone acetylation marks that have yet to be described in Apicomplexa. In very recent reports, low levels of H3 K79 acetylation have been detected in HeLa cells and Saccharomyces cerevisiae yeast (3,14), but the role of this novel mark has yet to be defined. The majority of H3 K79 is methylated in other species by Dot1, but intriguingly, Toxoplasma does not appear to possess a Dot1 homologue (36).…”
Section: Resultsmentioning
confidence: 99%
“…Acetylation of K23 and K79 on H3 and K31 on H4 are novel histone acetylation marks that have yet to be described in Apicomplexa. In very recent reports, low levels of H3 K79 acetylation have been detected in HeLa cells and Saccharomyces cerevisiae yeast (3,14), but the role of this novel mark has yet to be defined. The majority of H3 K79 is methylated in other species by Dot1, but intriguingly, Toxoplasma does not appear to possess a Dot1 homologue (36).…”
Section: Resultsmentioning
confidence: 99%
“…Chemically acetylated H2B protein was prepared based on previously published methods 29, 30 , which provides solution-accessible lysine residues as potential substrates. Briefly, 0.3 µmol of purified H2B was dissolved in 1 mL of freshly prepared 7 M urea solution with 500 mM ammonium acetate and 50 mM ammonium bicarbonate (pH 8.5).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies on the specificity of hSIRT1, using different types of peptide arrays (Blander et al, 2005;Garske and Denu, 2006), revealed no clear consensus sequence for acetyl-lysine recognition. In contrast to the multispecificity of hSIRT1, the substrate repertoire analysis of the ySir2 ortholog from S. cerevisiae revealed its narrow specificity toward conserved histone acetyl-lysine residues (Bheda et al, 2012). This observation suggests that multi-specificity in SIRT1 can be acquired or lost through evolution, nevertheless, its molecular basis is still unknown.…”
Section: Discussionmentioning
confidence: 93%